2019
DOI: 10.1039/c8cp05294h
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study on the interface morphology of vapor-deposited amorphous organic thin films

Abstract: The interfaces between amorphous organic layers play an important role in the efficiency and lifetime of organic light emitting diodes (OLEDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Several authors have demonstrated the presence of a higher degree of spatial and energetic disorder at the bulk-heterojunction interface, which rather represents a strongly intermixed phase. 9,48,49 To study the impact of the interfacial disorder on the charge carrier energetics, we apply a higher energetic disorder, σ int > σ bulk , at all interface sites as sketched in Figure 1. The density of states, g′(E), is now given by a superposition of the bulk DOS, g bulk (E), and the interface DOS, g int (E), with the percentage f of interface sites:…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have demonstrated the presence of a higher degree of spatial and energetic disorder at the bulk-heterojunction interface, which rather represents a strongly intermixed phase. 9,48,49 To study the impact of the interfacial disorder on the charge carrier energetics, we apply a higher energetic disorder, σ int > σ bulk , at all interface sites as sketched in Figure 1. The density of states, g′(E), is now given by a superposition of the bulk DOS, g bulk (E), and the interface DOS, g int (E), with the percentage f of interface sites:…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…However, a full ab initio model of the interfaces within the large photoactive layer is not feasible due to an enormous computational cost. Several authors have demonstrated the presence of a higher degree of spatial and energetic disorder at the bulk-heterojunction interface, which rather represents a strongly intermixed phase. ,, To study the impact of the interfacial disorder on the charge carrier energetics, we apply a higher energetic disorder, σ int > σ bulk , at all interface sites as sketched in Figure . The density of states, g ′( E ), is now given by a superposition of the bulk DOS, g bulk ( E ), and the interface DOS, g int ( E ), with the percentage f of interface sites: Figure shows the distributions of (a) hole and (b) electron energies for an interface energetic disorder varying from 25 to 100 meV at a constant disorder of σ bulk = 50 meV within the bulk of the photoactive layer.…”
mentioning
confidence: 99%
“…The understanding of the driving forces regulating molecular orientation is mandatory to optimize material properties, such as charge transport, and to design processes and/or compounds to improve device efficiency. In this matter, the molecular dynamics (MD) at atomic resolution is a powerful computational method able to rationalize the microscopic origin of the molecular preferred orientation, [ 17–26 ] and several studies have been reported to successfully study interfacial properties and molecular arrangement of OLED materials. [ 7,18,20,27 ] For a general description of the challenges and the strategies currently used in the computational modeling of OLED materials, we refer the interested reader to a recent perspective [ 19 ] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…They instead used a higher fullerene concentration than would be used experimentally to be able to qualitatively understand the behaviour at the interface [144]. Alternatively, Yoo et al [137] proposed the 'frozen-bulk' method for studies of interfaces in vapor-deposition simulations. They proposed that, at large distances from the interface and at a temperature lower than T g , the orientation of the bulk region does not significantly change.…”
Section: 13mentioning
confidence: 99%
“…They proposed that, at large distances from the interface and at a temperature lower than T g , the orientation of the bulk region does not significantly change. The motion of these regions was therefore frozen to allow for more efficient simulation [137]. Ratcliff et al [136] also used positional fixing to enhance computational efficiency for the MC simulation of vapor deposition.…”
Section: 13mentioning
confidence: 99%